MODELING OF SPATIAL-TEMPORAL VARIATIONS OF PHYSICAL PROCESS PARAMETERS IN THE IONOSPHERIC PLASMA OVER UKRAINE DURING THE MAXIMUM PHASE OF THE 24-TH SOLAR ACTIVITY CYCLE (2012—2015) - Kolodyazhnyi, V. V.; Lyashenko, M. V.; Emelyanov, L. Ya; Dziubanov, D. A. (Kosmìčna nauka ì tehnologìâ, 2024)
The object of research is physical processes occurring in the ionospheric plasma. The subject of research: spatial-temporal variations of the main parameters of the ionospheric plasma, which were obtained using incoherent scatter radar. Research methods include the ground-based radiophysical method of incoherent scatter of radio waves, statistical analysis of observation results, and semi-empirical modeling of parameters of dynamic and thermal processes. Modeling and analysis of spatial-temporal variations of the dynamic and thermal processes parameters in the ionosphere during the maximum phase of the 24th solar activity cycle (2012—2015) have been performed using experimental data obtained by the Kharkiv incoherent scatter radar. For the periods of the equinoxes and solstices, diurnal dependences of process parameters in the ionospheric plasma at altitudes from 210 to 450 km were constructed. The values of plasma transfer velocity due to ambipolar diffusion, the density of the full plasma flux, and the flux of charged particles due to ambipolar diffusion were determined. The values of the energy supplied to the electron gas, the density of the heat flux transferred by electrons from the plasmasphere to the ionosphere, as well as the velocity of the equivalent neutral wind and the meridional component of the neutral wind velocity, were calculated. It was established that for the considered periods, the effects of space weather variations and geomagnetic activity were significantly manifested in variations of the plasma flux density due to ambipolar diffusion, the density of the full plasma flux, as well as the energy supplied to electrons per unit time. Quantitative and qualitative characteristics of these parameters were typical but changed significantly (by 2…3 times) in some cases, even with a slight increase in geomagnetic activity.